2013
DOI: 10.1063/1.4819396
|View full text |Cite
|
Sign up to set email alerts
|

Imprint electric field controlled electronic transport in TlGaSe2 crystals

Abstract: The effect of built–in electric field onto the dc electrical conductivity, photoconductivity, and electrical switching phenomenon were investigated in TlGaSe2 layered semiconductor within the temperature range of 77–300 K. We have used different types of electrodes for different TlGaSe2 samples in both parallel and perpendicular directions to the plane of layers. The effect of electric field was investigated by cooling the samples from the room temperature under the electric field and then removing it at ∼80 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…As was shown in our previous investigations [20], the built-in electric field substantially increases the conductivity within the volume of the crystals as in the case of disordered semiconductors. We have shown that TlGaSe 2 behaves in many respects as a disordered semiconductor [20,21].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…As was shown in our previous investigations [20], the built-in electric field substantially increases the conductivity within the volume of the crystals as in the case of disordered semiconductors. We have shown that TlGaSe 2 behaves in many respects as a disordered semiconductor [20,21].…”
Section: Introductionsupporting
confidence: 74%
“…As was shown in our previous investigations [20], the built-in electric field substantially increases the conductivity within the volume of the crystals as in the case of disordered semiconductors. We have shown that TlGaSe 2 behaves in many respects as a disordered semiconductor [20,21]. So, the main experimental findings of the present work are based on the model which considers the TlGaSe 2 as a disordered semiconductor with a native thin insulating layer on its surface.…”
Section: Introductionsupporting
confidence: 74%
“…Таким образом, можно заключить, что электрическая неоднородность кристалла, сформированная в результате перестройки доменной структуры (поляризацией образца под действием внешнего поля в низкотемпературной сегнетофазе), сохраняется и в высокотемпературной области параэлектрического состояния кристалла, где эти неоднородности можно сопоставить исключительно с пространственно неоднородным заполнением ЦЛЗ. Эти данные хорошо согласуются с результатами ряда исследований различного рода эффектов памяти [5,[19][20][21][22][23][24][25].…”
Section: вариации фоточувствительности кристаллаunclassified
“…In a series of recent studies, [5][6][7] we have discovered the presence of a built-in internal electric field in TlGaSe 2 single crystals, which significantly changes the electronic transport properties of this material. The built-in internal electric field is pumped into the TlGaSe 2 by cooling the crystal from room temperature down to 77 K under the existence of an external electric field.…”
mentioning
confidence: 98%
“…It has been found that after the termination of the pretreatment in the electric field, a built-in internal electric field persists for a relatively long duration, even at temperatures well above the temperatures of phase transitions. 5 This built-in internal electric field is one of the most interesting yet not well understood phenomena in TlGaSe 2 semiconductor.…”
mentioning
confidence: 99%